Effect of Locally Administered Estradiol on Wound Healing in a Nasal Septal Perforation Animal Model - Yılmaz, Yetkin Zeki; Çakan, Dogan (Facial Plastic Surgery, 2023)
We aimed to investigate the effect of estradiol on wound healing in an experimental nasal septal perforation (NSP) model created in rats. Twenty-two Sprague Dawley healthy male rats were separated into two groups. NSP, approximately 2 mm in diameter, was created in each animal. The 0.1 mL 0.12% estradiol (12 g/L) (study group) and 0.1 mL 0.9% saline (9 g/L) (control group) were applied topically once a day for 14 days. The rats were sacrificed on the 14th day and the cartilage nasal septum of each animal was excised for histopathological examination. The nasal mucosal epithelial regeneration and degeneration, acute inflammatory cell count, fibroblast number, vascularization, granulation tissue formation, giant cell number, eosinophil number, degeneration and regeneration of the nasal cartilage, and collagen density were examined. The macroscopic closure rate of the perforations and histopathological parameters were evaluated statistically. In this study, the epithelial regeneration, the fibroblast count, the granulation tissue formation, and the amount of collagen were significantly higher in the study group than in the saline group (p < 0.05). The acute inflammatory activity was lower in the estradiol group than in the saline group (p < 0.05). There was no statistically significant difference in the closure rate of perforation between the two groups (p = 0.163). No significant difference was found in other comparisons (p > 0.05). The locally administered estradiol may improve wound healing of the nasal septum in an experimental NSP animal model.Level of Evidence Not applicable.
Keywords: experimental study; estrogen; nasal septal perforation; nasal; wound healing